Der unbequeme Bündnispartner. Zur selektiven Rezeption von Peter Weiss in der DDR - Rector, Martin (Studia Germanica Posnaniensia, 2018)
The topic ofthis article is the reaction of official GDR cultural policy to P. Weiss's conversion to Marxism that Weiss underwent between writing ,,Marat/Sade“ and „Ermittlung“' in the course of the year 1965. Rector suggests, that the GDR never managed to cleary define their attitude towards Weiss, because they were unable to accept his distinction between socialism as an inevitable development in world history and ,,real socialism“, that excludes freedom of opinium, particulary in the field of arts.